(untitled) (Palíndromo, 2013)
This paper presents analyses on a series of educative activities developed by the visual art exhibitions which were organized by Secretaria Municipal de Educação of Jacareí, in São Paulo, during the 90 ́s. In retrospective, this paper takes one of the seventeen exhibitions that are fully catalogued and registered and, by means of an analytical description of events, the article seeks to offer an understanding of the purposes which guided the elaboration of these projects, as well as to demonstrate how their planning, construction, reaching point, impact and resonances in time affected the teaching of arts. Thus, the main purpose here is to analyze the meaning of mediation as joined to educational formation in an amplified sense. Other sources and material are taken, such as official documents, interviews of people involved in the process, so that to offer a critical evaluation of the public politics of that period.